LOCAL KNOWLEDGE AND WISDOM IN THE JAVANESE SALVATION OF WOMEN PREGNANCY ‘MITONI’ (AN ETHOLINGUISTIC PERSPECTIVE) - Wakit Abdullah (Universitas Sebelas Maret, 2017)
Mitoni ‘a lifecycle salvation ceremony of the seventh month Javanese women pregnancy’ culturally well preserved and passed from generation to generations as an ethnolinguistic phenomenon. It is a descriptive and qualitative exploratory approach of the ethnoscience perspective. The data collection is done through techniques of in-depth interviewing and participant observation in ethnographic method. The data were analyzed using the ethnoscience model steps of analysis; the taxonomic, componential, and domain based on the cultural theme to reconstruct the phenomenon of language and traditions encompassing the local knowledge of the ritual ceremony. The results were divided into; (a) verbal expressions (pangucap 'words’') which strengthen the implementation of both the ritual offerings and ceremony of mitoni; (b) nonverbal expressions (patrap 'behavior') which include attitudes toward the ritual procession applying some required offerings such as jarik clothes along with the types, janur or yellow coconut leaves, water in a Jar (kendi), rice and chicken eggs in the sasserole. The life cycle ceremony mitoni aims to gain the ease and success for a mother in facing the birth process. Mitoni as a ritual ceremony includes the ritual function, social function, and the function of the preservation of traditions. It is found that the implementation life cycle ceremony mitoni turns the hearts’ of the practitioners tranquil as well as family providers can be trusted to provide life nobility.